Envelhecendo: experiências de pessoas idosas dos serviços de convivência sobre vínculos familiares, memória e cuidado - Spindola, Caroline dos Santos (Universidade Federal de São Carlos, 2026)
Old age is understood as a subjective marker that can generate anguish due to its association with death. As a complex social phenomenon, aging requires intersectoral policies, such as the National Social Assistance Policy, which promotes community and family interaction. This study aimed to understand the perception of aging, family bonds, memory, and digital sociability among elderly individuals attending community coexistence services in Piracicaba (SP). The following data collection methods were used: (a) a sociodemographic questionnaire, (b) a semi-structured clinical interview guide, and (c) an association diary. Through an exploratory, descriptive, and qualitative approach, 86 elderly individuals were interviewed (87% women, average age of 69 years). The participants, mostly retired with low education and income levels, showed an expanded concept of family, including affective bonds with relatives, neighbors, and even pets. Memory was valued as a testimony of life and as a bonding element. Internet use was seen mainly as a pastime, not as a community space. The body emerged as a central theme, marked by the duality between health and chronic pain. The birth of grandchildren and the independence of children were perceived as positive aspects, although feelings of abandonment were reported as negative experiences. Notably, the elderly did not spontaneously address the topic of aging and did not identify with their own age. The study concludes that public policies for old age must consider its subjective and relational dimensions, going beyond traditional approaches to effectively embrace the concrete experiences of the elderly.
Aging: experiences of older adults in social assistance services regarding family bonds, memory, and care
Envejeciendo: experiencias de personas mayores de los servicios de convivencia sobre vínculos familiares, memoria y cuidado
Keywords: Envelhecimento; Pessoas idosas; Pesquisa qualitativa; Assistência social; Políticas públicas; Aging; Elderly people; Qualitative research; Social assistance; Public policies; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar; 5. Igualdade de Gênero; 10. Redução das Desigualdades